Aptitude Measurement for Women’s Participation in Judo: Applied On female Aged 15 – 20 years Old - Tariq, Uoday; Nasser, Abeduljaleel (Journal of Physical Education, 2017)
problem of the research lies in the lack of female participation in judo in Iraq a matter that led the researchers to identify women’s aptitudes towards judo. They designed and applied a measurement on females aged 15 – 20 years old (166) female students were measurement sample and 159 female students were study subjects. The data was collected and treated using proper statistical operations. The researchers concluded that there is a general weakness among female participation in judo and the media and press increased this decline in participation. Social and religious had no positive effect in increasing female participation in judo. Psychological aspects including stress, risk, health and physical fitness had the most positive motivation to participate in judo. The researchers recommended the necessity of NOC, the ministry of Youth and sports, National federation of Judo to make strategies to attract females to this sport. In addition to that the researchers recommended sport media and press should present judo as a fun and health sport not only injures and separating armature judo from professional judo. Finally specialized schools for judo for females should be founded by the National Olympic committees a seed for more female national teams